Respuesta :

Answer:  [tex]\frac{2^{6}}{2^{8}}= 2^{-2}[/tex]    [tex]2x^{-2} =\frac{1}{4}[/tex]

[tex]\left(-6\right)^{6}\cdot\left(-6\right)^{-4}=36[/tex]

Step-by-step explanation:

When dividing by the same number with a different exponent, subtract the exponent in the denominator from the exponent in the numerator.

A negative exponent means to take the reciprocal of the power.

2² = 4  but since  it is [tex]2^{-2}[/tex]  the result is the reciprocal of 4 which is 1/4

When Multiplying the same base with different exponents, add the exponents.

6 + (-4) = 2  so   [tex]\left(-6\right)^{6}\cdot\left(-6\right)^{-4}[/tex]  becomes -6² = 36  

ACCESS MORE